Comparative morphology of tubular bones of Blagovarsky cross ducks in the postnatal period of ontogenesis - Oleksandra Pasnichenko; Zbihniev Sobek; Svitlana Tkachuk; Ivan Yatsenko; Roman Bokotko (Ukrainian Journal of Veterinary Sciences, 2022)
The microstructure of limb skeletal bones is closely related to ontogenetic age, localised skeletal growth dynamics, biomechanical modes of bone load, and possible taxonomic differences. This is important for the investigation of the problematic issues of ontogenetic changes in the compact bone tissue of domestic ducks. The purpose of the study was to compare the microstructure of the mid-diaphysis of the humerus and femur bones of Blagovarsky cross ducks, depending on age and gender. The material for research was the tubular bones of the thoracic (humerus) (n = 72) and pelvic (femur) (n = 72) limbs of Blagovarsky cross ducks aged 1 day, 10, 20, 30, 90, 196, 268, 341 and 483 days of postnatal ontogenesis of both sexual groups (females and males of 36 ducks each), a total of 72 ducks. The timing of the selection of ducks coincided with the technological cycle of their cultivation. Histological sections with a thickness of 5-10 microns were obtained, which were dyed with hematoxylin Karatsi and eosin, and according to Van Gieson for connective tissue differentiation. Morphometry determined the quantitative indicators of compact bone tissue in the middle of the diaphysis of tubular bones: the diameter of the diaphysis, the thickness of the periosteum, compact bone tissue, the diameter of osteons and central channels of osteons (Havers channels). It was discovered that the growth of the humerus and femur bones in length and thickness is completed on the 196th day of the postnatal period of ontogenesis in both female and male ducks. It was established that medullary (cerebral) bone tissue (1.01 ± 0.10 mm) appears from the femoral endostus of females, which is formed on the 196th day of the postnatal period of ontogenesis (the beginning of sexual maturity of females) and is further observed in intensive periods of their egg production on 268 and 341 days (2.43 ± 0.56 and 2.55 ± 0.62 mm, respectively), and disappears on the 483rd day (0.20 ± 0.03 mm) when the duck is not laying eggs. This study for the first time determined the age dynamics of morphometric parameters of microstructures of compact bone tissue of the humerus and femur and established their sex differences in ducks of the Blagovarsky cross. The results of comparative morphology studies are necessary for determining the age, sex, and species of birds based on the microstructure of compact bone tissue in the middle of the diaphysis of tubular bones, and for the ability to differentiate changes in the occurrence of limb pathologies in poultry